Analysis of the Influence of Progressive Wear of Helical Gear on Gear Vibration Characteristic - Xiuquan Sun; Tie Wang; Ruiliang Zhang; Fengshou Gu (Jixie chuandong)
At present， the traditional Archard wear model is mostly used to study the influence of wear on the dynamic characteristics of gears， without considering the lubrication characteristics of gears, and the main research objects are mostly straight gears. In order to make up for the shortage of research on helical gear， the wear process under mixed elastohydrodynamic lubrication is numerically simulated. An eight-degree of freedom dynamics model of helical gear is established to investigate the influence of tooth surface wear on gear dynamic characteristic. The gear fatigue test is carried out on a helical gearbox test rig to validate the numerical results. The results show that the wear mainly occurs on the region close to the tooth root and tooth tip， and the maximum wear occurs at the tooth root due to the relative high sliding-to-roll ratio. The variation of the amplitudes of the gear meshing frequency and its harmonics demonstrates that the wear causes an increase in gear vibrations. The experimental results show a good agreement with the numerical results， which implies the study can provide a reliable theoretical basis for the prediction and fault diagnosis of helical gear wear.